Growth and policy in developing countries : a structuralist approach - Ocampo, José Antonio (Initiative for Policy Dialogue at Columbia (Series), 2009)
Economic structuralists use a broad, systemwide approach to understanding development, and this textbook assumes a structuralist perspective in its investigation of why a host of developing countries have failed to grow at 2 percent or more since 1960. Sensitive to the wide range of factors that affect an economy's strength and stability, the authors identify the problems that have long frustrated growth in many parts of the developing world while suggesting new strategies and policies to help improve standards of living. After a survey of structuralist methods and post-World War.